2015
DOI: 10.1007/s00192-015-2772-z
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison between the Prolift and Elevate anterior vaginal mesh procedures: 18-month clinical outcome

Abstract: In conclusion, our results suggest that the use of the Elevate system in patients with anterior compartment prolapse results in fewer mesh erosions, but similar efficacy, compared with the Prolift mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
4
12
0
Order By: Relevance
“…Vaginal mesh exposure was previously identified among 21 (8.0%) of 264 women implanted with the Prolift system and 6 (8.5%) of 71 women implanted with the Elevate system . Obese patients are more technically challenging in terms of vaginal mesh placement than those without obesity, and high BMI has been associated with increased blood loss and mesh exposure . In the present study, both groups of patients had a mean BMI within the normal range—a finding that might have contributed to reduced risk of mesh exposure.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Vaginal mesh exposure was previously identified among 21 (8.0%) of 264 women implanted with the Prolift system and 6 (8.5%) of 71 women implanted with the Elevate system . Obese patients are more technically challenging in terms of vaginal mesh placement than those without obesity, and high BMI has been associated with increased blood loss and mesh exposure . In the present study, both groups of patients had a mean BMI within the normal range—a finding that might have contributed to reduced risk of mesh exposure.…”
Section: Discussionsupporting
confidence: 52%
“…The rates of new‐onset SUI in the present study were lower than those previously reported. Rogowski et al . found a rate of 11.5% in the Prolift group and 14.5% in the Elevate group.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Associated risk factors may include patient comorbidities, concomitant hysterectomy, and a junior surgeon, etc . Recent studies of Elevate reported consistently low (0‐6.3%) rates of vaginal mesh exposure but the influencing factors have not been explored yet . In this study, patient comorbidities, concomitant hysterectomies (more cases in the Elevate group) did not seem to affect the low exposure rate in the Elevate group, and that could be the result of using the new lightweight meshes and also a better surgeons’ experience when performing Elevate at a later period.…”
Section: Discussionmentioning
confidence: 57%
“…Most studies comparing transobturator meshes and Elevate Ant have shown equivalent success rates in the anterior compartment, but did not assess apical results. In a retrospective comparative study, Rogowski et al found a similar rate of 90 % good objective results (stage ≤1) in the anterior compartment in their Prolift and Elevate Ant groups at 18 months [22]. Feiner et al, in a study comparing the Prolift mesh and the Perigee mesh with a follow-up of just 11 months, found equivalent subjective and objective results [8].…”
Section: Discussionmentioning
confidence: 85%